113k views
0 votes
The function g(x) is defined as g(x) = -2x + 3x. The value of g(-3) is?

User Braunbaer
by
5.9k points

2 Answers

3 votes

Answer:

The value is -3

Explanation:

g(x) = -2x + 3x

You only need to substitute for x.

g(x) = -2x + 3x

g(-3) = -2(-3) + 3(-3)

g(-3) = 6 - 9

g(-3) = -3

User JohnBee
by
5.6k points
4 votes

Answer:

Explanation:

To find g(-3) all we have to do is plug the value of x = -3 into our function g(x)

So we have:

g(x) = -2x + 3x

So every place there is an x in that equation we are gonna put in a -3 because we want g(-3).

So: g(-3) = -2(-3) + 3(-3)

g(-3) = 6 - 9

g(-3) = -3

So we can say that when x = -3

g(-3) = -3

User Meriley
by
5.5k points